Path-Specific Effects. (22nd August 2017) - Weinberger, Naftali
Abstract: A cause may influence its effect via multiple paths. Paradigmatically (Hesslow [1976] ), taking birth control pills both decreases one's risk of thrombosis by preventing pregnancy and increases it by producing a blood chemical. Building on (Pearl [2001] ), I explicate the notion of a path-specific effect. Roughly, a path-specific effect of C on E via path P is the degree to which a change in C would change E were it to be transmitted only via P . Facts about such effects may be gleaned from the structural equations commonly used to represent the causal relationships among variables. I contrast my analysis of the Hesslow case with those given by theorists of probabilistic causality, who mistakenly link it to issues of causal heterogeneity, token causation, and indeterminism. The reason probabilistic theories misdiagnose this case is that they pay inadequate attention to the structural relationships among variables. 1 Introduction 2 Probabilistic Causality and Structural Causal Models 3 Cartwright and Eells Debate Birth Control 4 Defining Path-Specific Effects 5 Path-Specific Effects and Probabilistic Causality 6 Conclusion